I Botany Bay - Gwanas, Bethan (Y Lolfa, 2017)
Popular author Bethan Gwanas's latest novel set in Wales and Australia. Part fact, part fiction, it follows Ann Lewis, an ordinary girl who finds work at a local tailor shop, but her fall from grace isn't far away and leads to an epic journey. Reprint. First Published in 2015.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books